MAKNA SOSIAL DAN RELIGIUS TRADISI MAULID NABI PADA MASYARAKAT LOMBOK UTARA - Saparudin; Mokhammad Yahya; M. Aunul Hakim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The tradition of celebrating the Prophet's Birthday in the Sasak community of North Lombok is a form of local Islamic cultural heritage that has social and religious values ​​in community life. This study is important because the tradition of celebrating the Prophet's Birthday not only functions as a religious activity, but also serves as a means of cultural preservation and strengthening social relations in the community amidst the development of modernization. This study aims to analyze the social and religious meaning of the tradition of celebrating the Prophet's Birthday in the Sasak community of North Lombok and explain the form and implementation of this tradition in community life. This study uses a qualitative research method with a library research approach. Data were obtained from books, scientific journals, articles, and various literature related to the tradition of celebrating the Prophet's Birthday and Sasak culture. Data analysis was carried out descriptively-qualitatively through the process of collecting, grouping, and interpreting data according to the research focus. The results show that the tradition of celebrating the Prophet's Birthday in the Sasak community of North Lombok has unique forms of implementation, such as Praja Mulud, menyilaq, reading barzanji, and various other religious traditional rituals. These traditions contain social meanings in the form of strengthening solidarity, mutual cooperation, and family relations between residents. Furthermore, the tradition of celebrating the Prophet's Birthday also has religious significance as a manifestation of love for the Prophet Muhammad, a means of spiritual development, a medium for preaching, and Islamic education for the community. This research contributes to the development of local Islamic cultural studies and serves as a reference for the relationship between religion, culture, and social life in the Sasak community of North Lombok.